404: Civility Not Found? Evaluating the Effectiveness of Small Language Models in Detecting Incivility in GitHub Conversations - Patrício, Mário; Eufrásio, Silas; Uchôa, Anderson; Rocha, Lincoln S.; Coutinho, Daniel; Pereira, Juliana Alves; Paixão, Matheus; Garcia, Alessandro (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2025)
Context: Incivility in open-source software (OSS) platforms like GitHub can harm collaboration, discourage contributor participation, and impact code quality. Although current moderation tools based on Machine Learning (ML) and Natural Language Processing (NLP) offer some support, they often struggle to detect nuanced or implicit types of incivility. Goal: This study aims to assess the effectiveness of Small Language Models (SLMs) in detecting both coarse-grained (civil vs. uncivil) and fine-grained (specific types) incivility in GitHub conversations (issues and pull requests), and to understand how different prompting strategies influence detection performance. Method: We evaluate ten SLMs (3B-14B parameters) across five prompt strategies, on a labeled dataset with more than 6k GitHub conversations. We also compare the best-performing SLMs with five traditional ML models using two text-encoding techniques. Results: Our results reveal that SLMs perform well in detecting civil comments, but their effectiveness in detecting uncivil comments depends on model size. Models with 9B+ parameters (e.g., deepseek-r1, gpt-4o-mini) show improved performance on uncivil comments. For the fine-grained granularity, prompting strategy plays a critical role, with role-based prompting achieving the best results, particularly for implicit incivility types (e.g., Irony and Mocking), even when SLMs struggle with these types of incivility. Traditional ML models still perform well in explicit cases like Threat and Insulting. Conclusion: Our findings highlight the effectiveness of SLMs and prompt strategies in enhancing the detection of incivility within collaborative software development settings.